A Time-Memory-based CMOS Vision Sensor with In-Pixel Temporal Derivative Computing for Multi-Mode Image Processing - Jee, Dong Woo; Ko, Seong Min; Kasichainula, Kishore; Yeo, Injune; Cao, Yu; Seo, Jae Sun (European Solid-State Circuits Conference, 2023)
This paper presents in-pixel and near-pixel processing circuit techniques for multi-mode processing CMOS vision sensor. The new design includes a checkerboard patch-based pixel circuit and column-shared frame difference processing circuits that detect a patch-level temporal change and generate lb event signal. In-pixel time memory circuit is proposed to process a temporal derivative of the event in both area and power efficient way. The 324× 252 vision sensor is implemented in 0.18 μ m CMOS process and consumes 4.79 μ W @12.5fps showing FoM of 42.2pJ/pix. frame in the patch mode operation for frame difference-based motion detection and temporal derivative generation.
Keywords: Frame differences; Images processing; In-pixel processing; In-sensor computing; Multi-mode image processing; Multimodes; Nearpixel processing; Pixel processing; Sensor computing; Temporal derivatives; Vision sensors; frame difference; in-pixel processing; in-sensor computing; multi-mode image processing; nearpixel processing; temporal derivative; vision sensor